Раскройте скобки и выражение 5ab-(ab+(-5ab-(2ab-

лисичка73 лисичка73    2   13.03.2019 00:00    0

Ответы
SonyaCooling SonyaCooling  25.05.2020 03:06

незнаю правельно или нет но вот:

 

в)5ab-(ab+(-5ab-(2ab-1)))=5ab-(ab+(-5ab-2ab+1)))=

5ab-(ab+(-7ab+1)))=5ab-(ab-7ab+1))=

=5ab-(-6ab+1)=5ab+6ab-1=11ab-1

ПОКАЗАТЬ ОТВЕТЫ
recavkana recavkana  25.05.2020 03:06

5ab-(ab+(-5ab-(2ab-1)))=5аb-(ab+(-5ab-2ab+1))=5ab-(ab-5ab-2ab+1)=5 ab-ab+5ab+2ab-1=11ab-1

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика